Comparison of metal oxide and composite phase change material based nanofluids as coolants in mini channel heat sink. (October 2021) - Jitheesh, E.V.; Joseph, Mathew; Sajith, V.
Abstract: Present work focuses on heat transfer and pressure drop studies of Al2 O3 based nanofluids and nanoencapsulated composite phase change material (NECPCM) based nanofluids in mini channel heat sink. Composite PCM was prepared by homogeneously mixing paraffin wax and petroleum jelly. The encapsulation of composite PCM in polystyrene shells was done by mini emulsion polymerization and various characterizations were done to study phase change behaviour. The concentration of NECPCM and Al2 O3 nanofluids was fixed based on zeta potential measurements. Experiments were conducted in mini channel integrated with a heat sink, consisting of 13 rectangular channels and hydraulic diameter of 2.6 mm. Maximum heat transfer enhancement of 28% was obtained for NECPCM nanofluid against 10% enhancement for Al2 O3 nanofluid. Higher pressure drop was observed for Al2 O3 nanofluid as compared to NECPCM nanofluids, especially at higher flow rates. Maximum improvement in figure of merit (FOM) obtained for NECPCM nanofluid and Al2 O3 nanofluid was 24% and 5% respectively, as compared to DI water. The experimental results show that there exists an optimum flow rate for NECPCM based nanofluids to achieve maximum FOM, which depends on length of the channel and residence time of particles. Highlights: Study of heat transfer performance of phase change material (PCM) nanofluid and Al2 O3 nanofluid in minichannel heat sink. Synthesis of nanoencapsulated composite PCM by mini emulsion polymerization. Stability studies of PCM and Al2 O3 nanofluids using Dynamic light scattering system. Heat transfer enhancement of 28% and 10% for PCM and Al2 O3 nanofluids, respectively. Figure of Merit of 24% and 5% for PCM and Al2 O3 nanofluids, respectively.